MODERNIZING PRIMARY EDUCATION BASED ON THE STEAM APPROACH - Khasanova Asila (Modern American Journals, 2025)
This article analyzes the theoretical and practical aspects of modernizing primary education through the STEAM approach. In modern education, interdisciplinary integration has become a crucial issue in developing students’ critical thinking, creativity, and problem-solving skills. The article provides an in-depth discussion of the role, benefits, and implementation strategies of STEAM (Science, Technology, Engineering, Arts, Mathematics) in the primary education process. Additionally, based on advanced practices, the article examines the impact of the STEAM approach on students’ learning quality and motivation. The author draws conclusions based on theoretical analysis, pedagogical observation, and a review of relevant literature.
Keywords: STEAM, primary education, interdisciplinary integration, creative thinking, modern pedagogy, innovative methods, problem-based learning, critical thinking.